Impact of cobalt-60 gamma radiation source on electronic devices using Geant4 - Zakaria, Abd. Hafiz; Mohd Mustafah, Yasir; Abdullah, Jaafar; Khair, Nahrul; Hanafi, Ithnin (Elsevier, 2017)
This paper discusses the evaluation of performance of the Atmel Atmega328 under exposure of Cobalt-60(Co-60) source. Geant4 software is used to simulate the passage of particles through matter and calculate the absorb dose rate using Monte Carlo Methods. In the simulation using the Geant4 software, we vary the distance of IC from the source. Experiments also was conducted to measure radiation level of actual Cobalt-60 source using Atmel Atmega328 based Geiger Muller Tubes sensor. The result of the simulation experiments were discussed based on the inverse square law theorem. Following the advantages and limitations of this paper, some recommendations for future researchers were also presented